Glossary of biological terms as an alternative in the physical culture professional formation - Valia Alina Crespo-Almeira; Raydel Gámez García; Enrique Henríquez-Hernández (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
The work arises due to the necessity of a teaching aid for the students, professors and professionals of the Physical Culture. This work gives the chance to consult and to deep on the biological concepts related to the profession. In the Physical Culture majoring the subjects that correspond to the Biological Sciences represent the necessary specific basic formation to support the regularities that characterize the theory and the methodology of the physical activity and the sport training from the biological point of view, in the understanding of the professional's working object. The bibliography declared in the programs of the subjects related to the biological cycle is very wide and diverse. It doesn't answers to the professional of the Physical Culture directly, and consequently it makes difficult the concrete use of the biological concepts in function of the professional work. For this reason, the authors of this work proposes the elaboration of a biological concepts glossary with the necessary biological concepts for the profession, their definitions and illustrations, as an alternative in the Physical Culture professional formation. These biological concepts are organized alphabetically so that the glossary can be used in the individual studies, question clarifications or other cognitive necessities constituting a more reasonable, easier and quicker way of interacting with acquired knowledge and information.